Effects of grilling on cholesterol oxide formation and fatty acids alterations in fish - Tatiana SALDANHA (Ciência e Tecnologia de Alimentos, 2010)
Due to the adverse effects of the cholesterol oxidation products for the human health, the search of the occurrence and the quantification of these compounds in foods are considered of great importance. In this paper the effect of grilling in hake and sardine on cholesterol oxides formation and fatty acids alterations was investigated. The main fatty acids determined in both fishes were docosahexaenoic (DHA), oleic, eicosapentaenoic (EPA) and palmitoleic. The total lipids, fatty acids and cholesterol contents were decreased significantly (p < 0.02) after thermal treatment, with simultaneous increase of the cholesterol oxides contents. The cholesterol oxides determined in both species in the present study were: 19-hydroxycholesterol, 24(S)-hydroxycholesterol, 22(S) hydroxycholesterol, 25-hydroxycholesterol, 25(R)-hydroxycholesterol and 7-ketocolesterol. Besides the presence of the cholesterol oxides in raw fishes, there were a greater number of products resulting from the oxidation of cholesterol side chain, a fact rarely observed in foods.